Ten Priorities for Research Addressing the Intersections of Brain Injury, Mental Health and Addictions: A Stakeholder‐Driven Priority‐Setting Study - Cole J. Kennedy; Erica Woodin; Julia Schmidt; Janelle Breese Biagioni; Mauricio A. Garcia‐Barrera (Wiley, 2024)
ABSTRACT Objectives The purpose of this study was to engage key stakeholders in a health research priority‐setting process to identify, prioritize and produce a community‐driven list of research questions addressing intersectional issues on mental health and addictions (MHA) in acquired brain injury (ABI). Methods A multiphasic health research priority‐setting process was co‐designed and executed with community‐based stakeholders, including researchers, health professionals, clinicians, service providers, representatives from brain injury associations, policy makers and people with lived experience of ABI and MHA, including patients and their family members. Stakeholders' ideas led to the generation of research questions, which were prioritized at a 1‐day workshop. Results Fifty‐nine stakeholders participated in the priority‐setting activity during the workshop, which resulted in a rank‐ordered list of the top 10 questions for research addressing the intersections of ABI and MHA. Questions identified touched on several pressing issues (e.g., opioid crisis, homelessness), encompassed multiple subtypes of ABI (e.g., hypoxic‐ischaemic, mild traumatic), and involved different domains (e.g., identification, intervention) of health research. Conclusions This community‐driven health research priority‐setting study identified and prioritized research questions addressing the intersections of ABI and MHA. Researchers and funding agencies should use this list to inform their agendas and address stakeholders' most urgent needs, fostering meaningful improvements to clinical services. Patient or Public Contribution An 11‐person working group comprised of people with lived experience, service providers, researchers, healthcare professionals and other key stakeholders collaboratively developed and informed the scope, design, methodology and interpretation of this study. Over 50 community‐based stakeholders contributed to the research priority‐setting activity. One co‐author is a person with lived experience.